Marriage and parenthood (London : Friends' Book Centre)
1934-11 1934 1930s 22 pages BIBLIOGRAPHY. ALFRED ADLER. What Life Should Mean to You. 1932. 10/6 pp. 300. Allen & Unwin This book deals with every stage of the life of the individual in his relations with his fellows — as a child in the home, an adolescent, and an adult. POUL BJERRE. The Remaking of Marriage. 1931. 7/6. pp. 253 Williams & Norgate. A philosophical examination of the changing moral standards of the present day, presented from the standpoint of a high ideal. MARY BORDEN. The Technique of Marriage. 1933. 7/6. pp. 296. Heinemann. A "layman's" book on marriage, containing a good deal of sound common sense, and stimulating to thought even those who do not agree with its conclusions. BRITISH SOCIAL HYGIENE COUNCIL. Preparation for Marriage. 1932. 5/-. pp. 191. Jonathan Cape. A "handbook for advisers", primarily designed to make available for all leaders of youth the necessary scientific knowledge, but also of great use to the general reader. HAVELOCK ELLIS. The Psychology of Sex. 1933. 12/6. pp. 320. Heinemann. Discusses the anatomy, physiology, and psychology of reproduction, and particularly the normal and abnormal difficulties in connection with reproduction and love. — — — Little Essays of Love and Virtue. 3/6. pp. 180. A. & C. Black. Six essays dealing with friendship, love, and mutual understanding in a frank and critical spirit. *M.J. EXNER. The Sexual Side of Marraige. 1932. 6/-. pp. 232. Allen & Unwin. A discussion of the difficulties and maladjustments in marriage, with advice as to their cause and cure. *MICHAEL FIELDING. Parenthood: Design or Accident? 1930. 2/-. pp. 168. Noel Douglas. A simple and comprehensive survey of the present position in regard to contraceptives. *A.H. GRAY. Men, Women, and God. 1923. 3/6. pp. 200. Student Christian Movement. An excellent, all-round book dealing with love, marriage, children, divorce, and moral standards from the Christian standpoint. (18) 15X/2/478/6